2008
DOI: 10.1103/physrevb.77.054420
|View full text |Cite
|
Sign up to set email alerts
|

Near-edge x-ray absorption studies of Na-doped tetracyanoethylene films: A model system for theV(TCNE)xroom-temperature molecular magnet

Abstract: Near-edge x-ray absorption studies of Na-doped tetracyanoethylene films: A model system for the V(TCNE) x room-temperature molecular magnet, 2008, Physical Review B, (77), 054420. http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…A combination of RPE, PES, and near-edge x-ray absorption fine structure ͑NEXAFS͒ has shown that the upper valence states are V ͑3d͒ derived, exhibiting a significant hybridization between V ͑3d͒ and TCNE cyano carbons, while the lower conduction states are dominated by the ligand singly occupied molecular orbital ͑SOMO͒, with no hybridization with V-related states. 10,49 The character of the computed COs is in excellent agreement with these findings. This provides indirect support for the essential features of the structure model adopted here.…”
Section: B Electronic Structuresupporting
confidence: 78%
“…A combination of RPE, PES, and near-edge x-ray absorption fine structure ͑NEXAFS͒ has shown that the upper valence states are V ͑3d͒ derived, exhibiting a significant hybridization between V ͑3d͒ and TCNE cyano carbons, while the lower conduction states are dominated by the ligand singly occupied molecular orbital ͑SOMO͒, with no hybridization with V-related states. 10,49 The character of the computed COs is in excellent agreement with these findings. This provides indirect support for the essential features of the structure model adopted here.…”
Section: B Electronic Structuresupporting
confidence: 78%
“…The position of the C(1s) main peak is at slightly higher binding energy (286.8 eV) than the corresponding peak for alkali-doped TCNE (286.5 eV). 20,21 The N(1s) core levels are broadened as compared to the N(1s) of pure TCNE, similar to the case for thin films of V(TCNE) 2 . 14,22 The binding energy of the main N(1s) peak for the Ni(TCNE) films is slightly higher than the corresponding value for alkali-doped TCNE (398.8 eV).…”
Section: Resultssupporting
confidence: 59%
“…14,22 The binding energy of the main N(1s) peak for the Ni(TCNE) films is slightly higher than the corresponding value for alkali-doped TCNE (398.8 eV). 20,21 The Ni(2p) core level spectra for the normal flux and high flux Ni(TCNE) x along with pure Ni metal film are plotted in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The same occurs for the N K-edge ( Fig. 3(b)), which has its absorption onset at 397 eV [18]. The V L-edge (not shown here)…”
mentioning
confidence: 73%
“…3(a)) has its absorption onset located at 284 eV, originating from a transition to the LUMO of V(TCNE) x [9,18]. When Ni is deposited on V(TCNE) x , the absorption onset decreases in intensity.…”
Section: Ni/v(tcne) X Interfacementioning
confidence: 99%